[Papanastassiou 1]
dancing party, masquerade, "Loukia 1942-1943, baby with parents, breast-feeding, changing nappy having a bath, little girl with toys, first steps on "bridle", "Dad's bachelor days", girl at the lake, with mother, a funny scene of a cheerfull company, dance performance, 1943 child & father, barbecue, party in a big hall, 1947-1948, setting afloat, procession in Athens, orthodox priest, swimming competition, funny scenes